2009
DOI: 10.1002/ejoc.200900428
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis and Cytotoxic Activity of Some Symmetrical Disulfides Derived from the Quinolin‐4(1H)‐one Skeleton

Abstract: The preparation of novel organic disulfides containing the 2-(substituted phenyl)quinolin-4(1H)-one ring is described. The synthesis starts from thioanthranilic acid esterified with various bromoacetophenones. Cyclization of the resulting phenacyl thioanthranilates in trifluoroacetic acid afforded a mixture of 2-(substituted phenyl)-3-sulfanylquinolin-4(1H)ones and 3,3Ј-disulfanediylbis[2-(substituted phenyl)quinolin-4(1H)-ones]. Heating of the mixture in o-xylene gave 3,3Ј-[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…1 H NMR(500 MHz, CDCl 3 ) δ ppm 7.85 (d, J = 8.6 Hz, 1H), 7.11 (d, J = 1.1 Hz, 1H), 6.86 (dd, J = 8.0, 1.7 Hz, 1H), 6.24 (s, 1H), 5.85 (s, 2H), 3.87 (s, 3H), 3.44−3.35 (m, 2H), 1.63−1.53 (m, 2H), 1.39−1.28 (m, 4H), 0.89 (t, J = 6.9 Hz, 3H). 13 Methyl 2-Amino-4-(benzylcarbamoyl)benzoate (17). The compound was prepared according to the procedure described for compound 16 with the use of benzylamine.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR(500 MHz, CDCl 3 ) δ ppm 7.85 (d, J = 8.6 Hz, 1H), 7.11 (d, J = 1.1 Hz, 1H), 6.86 (dd, J = 8.0, 1.7 Hz, 1H), 6.24 (s, 1H), 5.85 (s, 2H), 3.87 (s, 3H), 3.44−3.35 (m, 2H), 1.63−1.53 (m, 2H), 1.39−1.28 (m, 4H), 0.89 (t, J = 6.9 Hz, 3H). 13 Methyl 2-Amino-4-(benzylcarbamoyl)benzoate (17). The compound was prepared according to the procedure described for compound 16 with the use of benzylamine.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Several studies have reported that flavonoid aza-analogs, derivatives of 2-phenyl-3-hydroxy-4­(1 H )-quinolinone (3-HQ), exhibit significant anticancer activities. However, until now, no study has described their molecular target. We hypothesized that 3-HQs, due to their structural similarity to other flavonoid derivatives, may serve as good ligands for interaction with eEF1A1.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolines are unique natural alkaloids that are widely found in plants, marine organisms and microorganisms. A number of quinoline alkaloids with excellent biological activity have been commercialized (Figure ), such as quinine, camptothecin, , and berberine. Quinoline is a bicyclic scaffold structure composed of a benzene ring and a pyridine ring. , Quinoline has many isomers or analogues (Figure ), such as 1,2,3,4-tetrahydroquinoline, 5,6,7,8-tetrahydroquinoline, decahydroquinoline, quinolin-4­(1 H )-one, quinolin-4­(3 H )-one, quinolin-2­(1 H )-one, 3,4-dihydroquinolin-2­(1 H )-one, isoquinoline, 1,2,3,4-tetrahydroisoquinoline, 5,6,7,8-tetrahydroisoquinoline, decahydroisoquinoline, isoquinolin-4­(1 H )-one, isoquinolin-1­(2 H )-one, 2,3-dihydroisoquinolin-4­(1 H )-one, 3,4-dihydroisoquinolin-1­(2 H )-one, 1,4-dihydroisoquinolin-3­(2 H )-one, and isoquinolin-3­(4 H )-one . The rich structure types and broad-spectrum biological activities greatly increase the flexibility of quinoline structure modification and derivatization and provide great potential for the discovery of new novel pesticides. …”
Section: Introductionmentioning
confidence: 99%
“…The same course of reaction was observed with phenacyl thioanthranilates and resulted in the formation of 3-sulfanylquinolin-4(1H)-ones II and the corresponding disulfides. 11 When the phenacylamides of anthranilic acid were subjected to acid-mediated cyclization, 3-aminoquinolin-4(1H)-ones III were obtained. 12 Finally, analogous behavior was recently described for phenacylamides of anilin-2-sulfonic acid to yield the benzothiazine-1,1-dioxides IV (Scheme 1).…”
mentioning
confidence: 99%